[3]Dendralene Synthesis: Rhodium(III)‐Catalyzed Alkenyl CH Activation and Coupling Reaction with Allenyl Carbinol Carbonate1. Issue 47 (2nd October 2013) - Wang, Honggen; Beiring, Bernhard; Yu, Da‐Gang; Collins, Karl D.; Glorius, Frank
<x xml:space="preserve">Abstract</x> [3]DendrAl(l)ene! A new synthesis of [3]dendralenes is based on a RhIII‐catalyzed alkenyl CH activation and coupling reaction with allenyl carbinol carbonates (see scheme; DG=directing group). A variety of [3]dendralenes with diverse substitution patterns are accessible with good efficiency. The reaction is highly stereoselective and compatible with different directing groups and numerous functional groups.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>